Freeter, Arafo, House Husband: Shifting Values of Hegemonic Masculinity and Emphasized Femininity in Four Japanese Television Dramas - Rouli Esther Pasaribu (Universitas Diponegoro, 2020)
This study examines the shifting values of masculinity and femininity in four Japanese television dramas: At Home Dad (2004), Around 40: Chuumon no Ooi Onna Tachi (2008), Freeter, Buy a House (2010), and Wonderful Single Life (2012). This study employs a qualitative method, conducting a descriptive analysis method using Connell’s concepts of hegemonic masculinity and emphasized femininity.The findings of this study focus on the following: 1). Characters in the four television dramas challenge the dominant discourses of masculinity and femininity by living as freeters, house husbands, and arafos, 2). To criticize hegemonic masculinity and emphasized femininity, these dramas depict the negative aspects of living a rigid lifestyle encompassed by traditional gender roles and feature main characters who show alternative lifestyles of masculinity and femininity. 3). Hegemonic masculinity and emphasized femininity values shadow the emergence of alternative masculinity and femininity in contemporary Japanese society.